Social Cohesion Potential of Pendalungan Communities Toward Urban Space Integration in Jember - Koesoemawati, Dewi Junita (Universitas Negeri Semarang, 2016)
Jember downtown has pendalungan social phenomenon as a form of cultural assimilation resulting hybrid of Javanese and Madurese as a local community identity. Pendalungan communities occupy in kampongs in the melting pot with limited space that evokes the activity collectively as the potential of social cohesion. The result of previous studies on hybrid pendalungan only terms of sociology and culture. Based on the above phenomenon, this research is study about social cohesion potential of Pendalungan community at urban space integration in Jember. The research objective was to determine the specific characteristic of pendhalungan community as a potential of social cohesion and to know the concept of the urban space integration of pendhalungan community. The research approach used in this study was qualitative and quantitative. Qualitative research approach was used by reading the urban through synchronic reading to explore the potential of social cohesion of pendalungan community culture which has implications in the formation of urban space. The space integration was presented using the access graph. The result showed that the urban space integration had average height and the dominant form of asymmetry distribution. The formation of urban space in the melting pot no separation between forms a continuous space and forms a break up space, so is created social cohesion. This conditions strengthen the high value of the space integration supported its social cohesion potential